Federated States of Micronesia : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Micronesia's economy is stagnating, as externally funded infrastructure projects are moving slowly. Difficulties in the business climate, in particular those related to land tenure issues, continue to hold back private sector development. Real GDP growth of about 0.1 percent is estimated for the fiscal year 2014. The Micronesian economy is projected to grow at 0.6 percent in the medium term, while risks on the outlook are tilted to the downside. Growth in 2015 is projected to remain subdued at 0.3 percent, while consumer prices are projected to further decline to negative 1.0 percent thanks to the continued pass through of low oil prices.